The employment of eThesaurus to facilitate reading comprehension among Malaysian ESL students - Wardatul Akmam Din; Suyansah Swanto; Asmaa Abdul Hameed Alsaqqaf (2017)
Reading comprehension has been highlighted as a problem among Malaysia ESL students. Many students while being proficient text decoders have difficulty comprehending text. When there is little to no emphasis on comprehension, on exploring the meaning behind the words, students are not actually reading but merely making the appropriate sounds. The use of thesaurus among second language learners is useful in enriching their vocabulary, in that it is not only useful in looking up for new words, but also in scaffolding reading comprehension. Utilizing the thesaurus, students will be able to understand the difficult words by referring to other words that have the same meaning as the referred word. Consequently, it could encourage students to empower and enrich their vocabulary in second language. The main finding of the study suggests that employing eThesaurus helps ESL readers in their comprehension of literary texts. The questionnaire was distributed to a sample of 35 students and the data collected were statistically analysed.